Understanding Physician Barriers in the Management of Lung Cancer in Nepal. Can Educational Intervention Make a Difference? - Shilpakar, Ramila; Pandey, Shama; Gurung, Jasmine; Acharya, Bibek (Journal of National Heart and Lung Society Nepal, 2024)
Background: Lung cancer is the leading cause of cancer morbidity and mortality in Nepal. A majority of patients present with advanced stage and some patients are never referred to an oncologist. Many factors contribute to this, including lack of oncology training and exposure. Herein, we evaluated the physician related factors contributing to the current scenario of lung cancer treatment in Nepal.Methods: A prospective survey in Internal Medicine programs across Nepal was performed. A structured, self-administered questionnaire focusing on physician’s behavior, practice, and attitude towards lung cancer was used. Results: Total 74 participants responded to the survey questionnaire. Only 3 out of 10 Internal Medicine programs had a compulsory oncology rotation. Multiple factors contributed to delay in diagnosis of lung cancer. 66 participants (91.6%) responded that they gave empirical anti-tubercular drugs (ATT) to patients with a non-resolving consolidative mass before they began evaluation for lung cancer; 22 % deferred CT scan before ATT. Multiple courses of antibiotics was a common practice in 62.5% participants. Misattribution of existing symptoms was common. 83.3% agreed that they treated smokers with respiratory symptoms initially as COPD with no consideration of lung cancer while 72.2% did not consider lung carcinoma in a middle-aged, never-smoker female with non-resolving consolidative mass. We also discovered that 36.1% of participants don’t refer elderly patients with lung cancer to an oncologist.Conclusion: Lung cancer remains a neglected disease in Nepal. There is an urgent need to overcome physician related barriers by oncology education for physicians and in training programs.